THE USE OF GOVERNANCE METHODS AND THEIR REFLECTION ON THE GROWTH OF CORPORATE PROFITS AN ANALYTICAL STUDY OF THE PERFORMANCE INDICATORS OF TWO SAUDI COMPANIES FOR THE PERIOD FROM 2015-2019 - Sikna Swadi Wadi (Scholar Express Journals, 2022)
Statement of the importance of using good and appropriate governance methods and to show the reflection of the governance methods on the companies that they adopt from others the most important conclusion reached by the research mechanism is that the adoption of governance methods leads to companies not bearing additional and large sums to ask stakeholders to use them in their organizational structure.
Keywords: Corporate government; governance methods; profit growth